Parasocial interactions with media characters: the role of perceived and actual sociodemographic and psychological similarity - Möri, Michelle; Fahr, Andreas (Frontiers in Psychology, 2023)
Introduction Similarity between media character and viewer is an important predictor of parasocial interactions. Thereby, similarities are often limited to single characteristics or to the similarities viewers perceive between themselves and characters. This article expands the existing literature in two ways. First, the effects of actual and perceived similarity on parasocial interactions are compared. Second, similarity is understood in a broad way. With age, gender, job, relationship, and living situation are assessed for sociodemographic similarities. Psychological similarities are considered with the Big Five personality traits, loneliness, and self-esteem. Methods The study employs a multimethod design with a field study using tracking data, experience sampling surveys, and content analysis. With the content analysis, characters’ characteristics can be indicated independent from the viewers to assess actual similarity in a more objective way. Results In these everyday viewing settings, parasocial interactions increased with similarities in extraversion and perceived Big Five traits and decreased with similarities in age and consciousness. The other assessed similarity types did not influence parasocial interactions. Discussion Taken together, the study underlines the importance of differentiating between actual and perceived similarity when analyzing viewer PSI with media characters, and to specify the particular type of similarity.